Pengaruh NPL,CAR,LDR, dan BOPO Terhadap Profitabilitas (ROA) Bank Kalbar Selama 10 Tahun Terakhir (Periode 2003 s/d 2012) - B61112019, R.S.M. Al Amin B.A (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT This research is done to have test and analyze NPL, CAR, LDR and BOPO influence to profitability Bank Kalbar in last 10 years (periode 2003 – 2012) Data in this research was secondary data from financial publication report Bank Kalbar for every three months in 2003 – 2012 which has been published to Bank Indonesia and reported in mass media. Sampling technic used in this research was Purpose Sampling with criteria of total sample financial report about 40. Instrument analysis were using Classical Asumption Test, there are Multikolinieritas, Heterokedastisitas, and Autokorelasi, beside that, Statistical Analysis such as T test, F Test and R2 test were used. During observation periode, data through Classical Assumption Test shown has fulfill the requisite to use double linier regretion equation. Analytical results shown that, NPL, Car, LDR and BOPO influence the ROA about 56.60 %, meanwhile 43.40 % by another variable. F test about 8.8859 with probability 0.000 reported NPL, CAR, LDR and BOPO influence ROA variable together because the probability value below 0,05 with trusted about 95 %. The individual test results NPL, CAR, LDR variable was not significantly influence to ROA variable, except BOPO variable give significant influence to ROA variable. Keyword : NPL, CAR, LDR, BOPO, Profitability (ROA) Bank Kalbar